2010
DOI: 10.1086/652864
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Clinical Trial of Zinc Supplementation to Prevent Immunological Failure in HIV‐Infected Adults

Abstract: Background Adequate zinc is critical for immune function; however, zinc deficiency occurs in >50% of HIV-infected adults. We examined the safety and efficacy of long-term zinc supplementation on HIV disease progression. Methods A prospective randomized controlled clinical trial was conducted with 231 HIV+ adults with low plasma zinc levels (<0.75 μg/ml), randomly assigned into zinc (12 mg of elemental zinc for women and 15 mg for men) or placebo, for 18 months. The primary endpoint was immunological failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 36 publications
(47 reference statements)
4
128
1
7
Order By: Relevance
“…terms of development and productivity, generating physically challenged adults with low levels of productivity (22).…”
Section: Discussionmentioning
confidence: 99%
“…terms of development and productivity, generating physically challenged adults with low levels of productivity (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies the percentage of patients with virological control and the absence of other confounding factors is low [3,9].…”
Section: Commentsmentioning
confidence: 96%
“…29,33,34,[53][54][55] Although a Cochrane review 56 found no definite evidence of the role of nutritional supplementation on morbidity, mortality, and HIV disease progression among PLWH, and vitamin A supplementation seems to be beneficial only in children, subsequent reports from RCTs of supplementation have found benefits for both adults and children. [23][24][25]39,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] ART and nutritional supplementation are not in contradiction, as concluded by another review, 73 as each of them support the recovery of the immune system by different mechanisms.…”
mentioning
confidence: 92%
“…10 In the era of ART, wasting is more frequently observed in cases with virologic and/or immunological failure, who are living in poor socioeconomic conditions and with high food insecurity. 10,39 Micronutrient deficiencies have also been observed, even in patients receiving chronic ART. Jones et al 40 reported a high prevalence of zinc deficiency in participants on ART, adjusting for parameters of acute-phase reaction.…”
Section: Introductionmentioning
confidence: 99%